Evaluation of Potato Crisps Fried in Market Samples of Palm Olein, Corn Oil and Soya Oil - Augustin , M. A.; Heng, L. K.; Idris, Nor Aini (1988)
The shelf life of potato crisps fried in market samples of palm olein, corn oil and soya oil was evaluated by a sensory panel comprising Malaysian panelists. The shelf-life of crisps fried in palm olein was significantly longer than those fried in soya oil (p <0.05). There were no significant differences (p < 0.05) between the shelf-life of crisps fried in palm olein and those fried in corn oil. In each oil system, the shelf-life of the crisps fried in the oils decreased with an increase in fry number. The shelf-life of the crisps fried in each oil was infuenced by the level of%polar components and the acid value of the oil.